(untitled) (Praxis Educativa, 2012)
The aim of this paper is to make a description of the process in which the National Education Law Nº 26206 (NEL) was promulgated and to make a critical comparative analysis of some topics regulated by that law to point out continuities and differences with the Federal Law of Education Mº 24521. The analysis is focused, on the one hand, on the political style of the NEL based on decisions rather than on deliberations and, on the other hand, on aspects regarding the governability of the education system. The topics were chosen giving priority to those connected with the distribution of attributions among the different education agents.